An investigation of green tea’s effect on mackerel (Scomber Scombrus)’s protein structure during frozen storage by FT-Raman spectroscopy - Rabia Alghazeer; Alansari, Wafa Suliman; Ghalia Shamlan; Areej A. Eskandrani; Nazlin K. Howell (Kuwait Journal of Science, 2021)
FT-Raman spectroscopy (FT-RS) was used to investigate green tea’s potential protective effect as an antioxidant during frozen storage of Atlantic mackerel (Scomber scombrus). Atlantic mackerel was stored for more than 26 weeks at −10 or–80°C (control), with or without green tea (GT). Raman analysis showed substantial protein structure changes due to frozen storage, especially at a higher storage temperature (−10°C), compared with −80°C or −10°C with instant GT, indicated by a decrease in the tyrosine doublet ratio, alpha helix content and O-H stretching bands intensities, along with an increase in tryptophan band intensity and β sheet structure. Using GT as antioxidant, at concentrations of about 250 ppm, can protect the fish protein structure for a limited storage period. However, for optimum freshness, fish should be stored at very low temperatures.